A study of the effect of deposition conditions on the phase-structural state of ion-plasma WC – TiC coatings - Sоbоl`, Oleg; Dur, Osman (Eastern-European Journal of Enterprise Technologies, 2019)
Studies of the influence of thermal and radiation factors on the elemental composition and phase-structural state of WC-TiC ion-plasma condensates of a quasibinary system are presented. As a thermal factor, we used different substrate temperatures during deposition and temperatures of high-temperature annealing of coatings after their deposition. The influence of the radiation factor was changed by applying a negative bias potential of different magnitudes to the substrate during coating deposition. It was found that with a change in the substrate temperature during deposition (in the temperature range 80–950 °C), a change occurs in the elemental composition of the coating. With an increase in the deposition temperature, the relative content of heavy metal atoms W increases and the relative content of Ti and C atoms decreases. At the phase-structural level, this leads to a change from the single-phase state ((W, Ti)C supersaturated solid solution at a deposition temperature of less than 700 °C) to two-phase ((W, Ti)C and α-W2C phases at a deposition temperature of more than 700 °C). The use of high-temperature annealing of coatings after their formation showed a relatively low decay activation efficiency. At an annealing temperature of 800 °C, a noticeable change in the phase-structural state is not observed, and at the highest temperature of 1000 °C and holding for 2 hours, the content of the α-W2C phase is relatively small and does not exceed 15 vol %. The supply of a bias potential stimulates the formation of a two-phase state from (W, Ti)C and α-W2C phases with nanometer crystallite size. With an increase in the bias potential from –50 V to –115 V, the average crystallite size decreases from 4.5 nm to 3.8 nm. The use of structural engineering methods in the work to create two-phase materials based on a quasibinary WC-TiC system is the basis for increasing the strength and crack resistance of coatings of such systems